ANALISIS FAKTOR FAKTOR YANG MEMPENGARUHI MINAT BERWIRAUSAHA (Studi Kasus Masyarakat Kelurahan Lubuk Pakam Deli Serdang) - Raden Mustika Septia Devi; Wan Dian Safina (JEKKP (Jurnal Ekonomi, Keuangan dan Kebijakan Publik), 2021)
This study aims to determine the influence of internal factors, external factors and emotional factors on the interest in entrepreneurship in the Lubuk Pakam Deli Serdang Village Community. The sampling technique used the slovin sampling method, namely the sample selected by the slovin formula amounted to 90 people. Methods of data collection using a questionnaire. The results of the simultaneous hypothesis test (F test) variable internal factors, external factors and emotional factors have a positive and significant effect on interest in entrepreneurship. In the partial hypothesis test (t test) the variables of internal factors, external factors and emotional factors have a positive and significant effect on interest in entrepreneurship. The results of the determination test were obtained. The coefficient of determination (R2) was 61.6% and the remaining 38.4%. This shows that the variables of internal factors, external factors and emotional factors have a positive and significant relationship with entrepreneurial interest. The results of the F test show that fcount is 6.495, while ftable is 0.207. This means that H0 is rejected and Ha is accepted, because fcount ftable, it can be interpreted that internal factors, external factors and emotional factors have a significant effect on entrepreneurial interest.